Enhanced photocatalytic degradation of Rhodamine B using polyaniline-coated XTiO3(X = Co, Ni) nanocomposites - Mariyem Abouri; Abdellah Benzaouak; Mohamed Elouardi; Lahcen El Hamdaoui; Fatima Zaaboul; Khalil Azzaoui; Belkheir Hammouti; Rachid Sabbahi; Shehdeh Jodeh; Mohammed Alaoui El Belghiti; Adnane El Hamidi (Scientific Reports)
Abstract In this study, novel polyaniline-coated perovskite nanocomposites (PANI@CoTiO3 and PANI@NiTiO3) were synthesized using an in situ oxidative polymerization method and evaluated for the photocatalytic degradation of Rhodamine B (RhB) a persistent organic pollutant. The nanocomposites displayed significantly enhanced photocatalytic efficiency compared to pure perovskites. The 1%wt PANI@NiTiO3 achieved an impressive 94% degradation of RhB under visible light after 180 min, while 1wt.% PANI@CoTiO3 reached 87% degradation under UV light in the same duration. X-ray diffraction (XRD) confirmed that the crystalline structures of CoTiO3 and NiTiO3 remained intact post-polymerization. At the same time, Fourier transform infrared spectroscopy (FTIR) verified the successful deposition of PANI through characteristic functional group vibrations. Diffuse reflectance spectroscopy (DRS) revealed reduced band gaps of 2.63 eV for 1wt.% PANI@NiTiO3 and 2.46 eV for 1wt.% PANI@CoTiO3, enhancing light absorption across UV and visible ranges. Scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDS) analysis demonstrated the uniform distribution of PANI, ensuring consistent surface activity and efficient charge transfer. The photocatalytic test confirmed a pseudo-first-order degradation mechanism. The study elucidates the degradation mechanism through intermediate identification via HPLC-MS analysis, highlighting N-de-ethylation, aromatic ring cleavage and eventual mineralization into CO2 and H2O as critical pathways. Furthermore, the 1wt.%PANI@NiTiO3 nanocomposite demonstrated excellent stability and recyclability, maintaining its degradation efficiency over four consecutive cycles with minimal change. These findings highlight the potential of PANI@XTiO3 nanocomposites for sustainable and efficient wastewater treatment, addressing diverse environmental challenges by tailoring photocatalysts to specific light sources.